Assessing Livelihood Capitals to Adapt with Saline Intrusion of Households in the Red River Delta: a Case Study in Dong Thuy Anh Commune, Hung Yen Province - Thi Ha Thanh, Nguyen; Phuc Anh Khue, Nguyen; Tien Giang, Nguyen; Quang Thanh, Bui; Le Tuan, Pham; Ngoc Tu, bui; Huu Duy, Nguyen (VNU Journal of Science: Earth and Environmental Sciences; Vol 41 No 4DO - 10.25073/2588-1094/vnuees.5320, 2025)
T his study was conducted to assess the current livelihoods and adaptive capacity of coastal farming households in Hung Yen province under the influence of saline intrusion, with a focus on Dong Thuy Anh commune. Findings from a social survey with 102 valid questionnaires indicate that aquaculture households performed greater flexibility in adapting to saline intrusion compared to crop‐producing households who experience higher levels of livelihood vulnerability. The correlation analysis reveals positive relationships among farmland area (natural capital), agricultural income (financial capital), and machinery investment value (physical capital), underscoring the importance of production scale for income generation and the effectiveness of technological investment. In addition, local supports also play a crucial role in moderating the impact of saline intrusion on household livelihoods. The distinct characteristics of livelihood activities and varying adaptive capacities to saltwater intrusion in the study area highlight the need for locally tailored response and support policies.